Molecular mechanism of salinity and waterlogging tolerance in mangrove Kandelia obovata - Liu, Huizi; An, Xia; Liu, Xing; Yang, Sheng; Liu, Yu; Wei, Xin; Li, Xiaowen; Chen, Qiuxia; Wang, Jinwang (Frontiers in Plant Science, 2024)
Mangrove forests are colloquially referred to as "Earth's kidneys" and serve many important ecological and commercial functions. Salinity and waterlogging stress are the most important abiotic stressors restricting the growth and development of mangroves. Here, we studied the morphological and transcriptomic responses of Kandelia obovata (K.obovata), the greatest latitudinally-distributed salt mangrove in China. By examining root morphological parameters and biomass accumulation under salt and waterlogging stress, we observed that both high salinity and waterlogging significantly inhibited growth and development in K. obovata. Notably, growth was negatively correlated with salt concentration and positively correlated with waterlogging duration, and high salinity was significantly more inhibitive than waterlogging. A total of 7,591 salt-responsive and 228 waterlogging-responsive differentially expressed genes were identified by RNA sequencing. We identified core salinity-and waterlogging-responsive modules through weighted gene co-expression network analysis of the combined gene expression and phenotypic datasets. Overall, long-term salt stress was highly correlated with the measured physiological parameters while long-term waterlogging was poorly correlated with these traits. At the same time, 45 salinity-responsive and 16 waterlogging-responsive core genes were identified. All 61 core genes were mainly involved in metabolic and biosynthesis of secondary metabolites pathways. This study provides valuable insight into the molecular mechanisms of salinity and waterlogging tolerance in K. obovata, as well as a useful genetic resource for the improvement of mangrove stress tolerance using molecular breeding techniques.